Differentiate \(f(x) = 12 + 7x\) from first principles.

Differentiate \(f(x) = 5x + 1\) from first principles.

Differentiate \(f(x) = 2 - 5x\) from first principles.

Differentiate \(f(x) = 7 - 3x\) from first principles.

Differentiate \(f(x) = 5x - 3\) from first principles.

Differentiate \(f(x) = x^2\) from first principles.

Differentiate \(f(x) = x^2 + 1\) from first principles.

Differentiate \(f(x) = 3x^2 - 1\) from first principles.

Differentiate \(f(x) = x^2 - x\) from first principles.

Differentiate \(f(x) = x^2 + 3x\) from first principles.

Differentiate \(f(x) = 3x - x^2\) from first principles.

Differentiate \(f(x) = x^2 - 4x\) from first principles.

Differentiate \(f(x) = x^2 + 6x + 2\) from first principles.

Differentiate \(f(x) = x^2 - 3x + 7\) from first principles.

Differentiate \(f(x) = x^2 + 5x - 7\) from first principles.

Differentiate \(f(x) = x^2 + x - 3\) from first principles.

Differentiate \(f(x) = 3x^2 - 5x + 7\) from first principles.

Differentiate \(f(x) = x^3\) from first principles.

Differentiate \(f(x) = \sqrt{x}\) from first principles.

Differentiate \(f(x) = \sqrt{x + 1}\) from first principles.

Differentiate \(f(x) = \dfrac{1}{x}\) from first principles.

Differentiate \(f(x) = \dfrac{1}{\sqrt{x}}\) from first principles.

Differentiate \(f(x) = \dfrac{2}{x}\) from first principles.

Differentiate \(f(x) = \dfrac{4t}{t + 1}\) from first principles.

Differentiate \(f(x) = \dfrac{x - 1}{x + 1}\) from first principles.